Troska o wellbeing matek jako antidotum wobec rezygnacji z rodzicielstwa młodych dorosłych - Linek, Anna (Kultura-Społeczeństwo-Edukacja, 2024)
The aim of the article is to show the role of the mother in the eyes of young people in the context of their procreation plans. Based on available research reports, they notice a decrease in interest in having a child, which, according to sociologists and psychologists, results from many different reasons. The presented analysis assumes that the mother’s image may contribute to this condition. Her role in the children’s lives is extremely important and she enjoys great authority in their eyes, giving them the support they need, but this involves certain costs on her part. The text refers to the results of existing research, from which emerges a picture of a tired, stressed mother who does not have time to take care of her health and other important needs, which may largely contribute to the decline in interest in copying such a pattern by young people who may not feel ready to make a similar sacrifice. The key point in this study is to point out the need to take broadly understood care aimed at the well-being of mothers – starting from themselves, so that they are more likely to take into account their own health, well-being and satisfaction, to broader social awareness and a whole range of activities in many fields of social life – so their children could see them primarily as happy women and have such an image of their own future.